Pemahaman Kembali terhadap Audit Sumber Daya Manusia (Studi Kasus di PT Sinar Baru Corporation) - Yayan Firmansah (University of Darussalam Gontor, 2015)
Human resources have a central role in achieving the company’s strategic objectives. As with other resources, the human resources are often also found problems, so we need checks to overcome these problems so as not to interfere with the achievement of the strategic objectives of the company. PT Sinar Baru Corporation is currently facing considerable problems of human resources management attention. Human Resource and General Affairs believes that these problems are not likely appear suddenly, but might be caused by something. Therefore, before determining the steps to resolve the issue, Human Resource and General Affairs would like to know in advance three causes such problems by conducting a human resource audit. The study uses a qualitative approach to the type of descriptive case study. This study uses interviews, observations, and documentation as data collection techniques. Key informants in this study are the Human Resource and General Affairs Manager and two auditors. The research concludes that there is a basic foundation that is misunderstood by the company, which the company considers that the object of HR audit is human, not the policy. This point of view makes the results of the program implemented are ineffective, beacuse the program leads to the recruitment and selection, and performance assessment rather than HR audit.